Encountering development : the making and unmaking of the third world - Escobar, Arturo, 1951- (Princeton University Press, 2012)
How did the industrialized nations of North America and Europe come to be seen as the appropriate models for post-World War II societies in Asia, Africa, and Latin America? How did the postwar discourse on development actually create the so-called Third World? And what will happen when development ideology collapses? To answer these questions, Arturo Escobar shows how development policies became mechanisms of control that were just as pervasive and effective as their colonial counterparts. The development apparatus generated categories powerful enough to shape the thinking even of its occasion.